Spatial sero‐prevalence of brucellosis in small ruminants of India: Nationwide cross‐sectional study for the year 2017–2018. Issue 4 (18th October 2020) - Shome, Rajeswari; Kalleshamurthy, Triveni; Rathore, Yashaswini; Ramanjinappa, Kavana D.; Skariah, Somy; Nagaraj, Chaitra; Mohandoss, Nagalingam; Sahay, Swati; Shome, Bibek Ranjan; Kuralayanapalya P., Suresh; Roy, Parimal; Hemadri, Divakar
Abstract: Brucellosis in small ruminants caused mainly due to Brucella melitensis is an important zoonotic disease characterized by abortion, retained placenta, infertility, orchitis, epididymitis and rarely arthritis. Small ruminants are the main source of economy for the rural and marginally poor farmers and brucellosis is resulting in huge economic losses due to abortions and infertility and causing public health concern among the small ruminant keepers. Bovine brucellosis control programme has been implemented in India and small ruminants are left out of the programme mainly due to paucity of brucellosis status. The present cross‐sectional study based on stratified random sampling was undertaken during 2017–18 to provide the nationwide brucellosis sero‐prevalence in small ruminants. A total of 24, 056 small ruminant serum samples (sheep samples = 8, 103 [male—2, 440 and female—5, 663] and goat samples = 15, 953 [male—4, 331 and female—11, 622]) sourced from 27 out of 29 states and two out of seven union territories (UTs), 350 districts of total 640 districts (54.68% of the Indian districts) and from 1, 462 villages out of 6, 40, 867 villages (43.83% of the Indian villages). The serum samples were tested by indirect ELISA and overall brucellosis apparent and true prevalence of 7.45 (95% CI: 7.13–7.79) and 3.79 (95% CI: 3.44–4.17) was recorded. Significantly higher brucellosis sero‐prevalence ( p < .0001) was observed in sheep (11.55%) than goats (5.37%). Similarly, brucellosis seropositivity was highly significant in females compared to males in both sheep and goats. Countrywide, greater than 5% brucellosis sero‐prevalence in sheep and goats was recorded in 14 and 10 states, respectively, indicating endemicity of the disease. The study provided the latest update on nationwide spatial sero‐prevalence of small ruminant brucellosis which will aid government to strengthen regular surveillance and vaccination to reduce the disease burden and public health problems in the country.